Politicians in disguise and financial experts on the board: Evidence from Spanish cajas - Pablo de Andrés; Inigo Garcia-Rodriguez; M. Elena Romero-Merino; Marcos Santamaria-Mariscal (BRQ Business Research Quarterly, 2021)
This study offers insight into the role of board politicization on the Spanish cajas' performance from a dual perspective. First, we analyze the effect of a new kind of political directors who occupy board seats as representatives of stakeholders outside the public administrations while maintaining a political affiliation. We call these "hidden" political directors as politicians in disguise. Second, we analyze how political interests can prevent directors with financial expertise from applying their knowledge to improve cajas' performance. Using a sample of hand-collected data from 45 Spanish cajas, we find that politicians in disguise destroy value in the caja and that politically motivated financial experts on the board do not benefit cajas' performance.
Keywords: G34; G21; G28; 650; Board composition; cajas; financial experience; politicians; savings banks